(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Social networking websites serve the purpose of connecting with each other. But nowadays it serves various other uses such as marketing purpose, shopping platform, review engine and many more. The main aim of the present paper is to explore the factors that affect the customers visit towards the restaurant influenced due to reviews mentioned on the social networking websites. Primary data was collected from 332 respondents belonging to the cities such as Mathura, Agra, Firozabad, and Allahabad. Non disguised questionnaire was used for the data collection purpose. Exploratory factor analysis has been applied on the collected data. The results of the study found five factors such as SNS Engagement, Conformity to trend, Social Prestige, Quality Perception, social influence on SNS which are affecting the customer’s views towards restaurant reviews.